Implementasi Sistem Informasi Pembayaran SPP Berbasis Web Dengan Metode SDLC Waterfall Studi Kasus Di SMA Al Maghfirah - Siti Nurjanah Faujiah (DPPM Universitas Pelita Bangsa, 2022)
One tangible form or realization of the use of dynamic web programming is in terms of making an information system that is used as a tool in the management of student payment administration in a school. In this case, the Administration or the finance department can later use it as inputting student payment data while carrying out learning activities at the school. At Al Maghfirah High School (SMA Al Maghfirah), in terms of recording student tuition payments, they still use recording in the ledger and Microsoft Excel assistance in their financial recap. Students will fill out a payment form then give it to the financial administration section. With these activities, from the financial officer's point of view, they will carry out a lot of work processes such as storing forms paid by students, recording them in a ledger, recapitulating them on the computer and even making reports that will be given to the principal. The results of this study are a student tuition payment information system that is able to manage student tuition payment information, facilitate payment information for students and make reports for payment officers or the finance department every period. By creating a web-based information system using the SDLC Waterfall system development method, it is hoped that it can help the process of paying tuition fees for students at SMA Al Maghfirah Cikarang Bekasi. Keywords: Waterfall, System Development Life Cycle, SDLC, Payment